Right-Wing Populism in Europe Politics and Discourse - Wodak, Ruth; KhosraviNik, Majid; Mral, Brigitte (Bloomsbury Academic, 2013)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Right-wing populist movements and related political parties are gaining ground in many EU member states. This unique, interdisciplinary book provides an overall picture of the dynamics and development of these parties across Europe and beyond. Combining theory with in-depth case studies, it offers a comparative analysis of the policies and rhetoric of existing and emerging parties including the British BNP, the Hungarian Jobbik and the Danish Folkeparti. The case studies qualitatively and quantitatively analyse right-wing populist groups in the following countries: Austria, Germany, Britain, France, Sweden, Norway, Denmark, Italy, Netherlands, Hungary, Belgium, Ukraine, Estonia, and Latvia, with one essay exclusively focused on the US. This timely and socially relevant collection is essential reading for scholars, students and practitioners wanting to understand the recent rise of populist right wing parties at local, countrywide and regional levels.